Sistem Informasi Perjalanan Dinas Berbasis Web (Studi Kasus Dinas Kominfo Dan Statistik Provinsi Bengkulu) - Dinda Khairunisa; Muhammad Imanullah; Yulia Darmi; Muntahanah Muntahanah (Jurnal Media Infotama, 2025)
Official travel is a trip for the benefit of the office from the order of the superior authorized to order. Based on the results of interviews, problems in making letters relating to official travel are increasingly being found so that it requires the existence of an official travel order management application. The Application for Management of Official Travel Warrants is an application that will be used to facilitate the management of all important documents related to official travel carried out by the Dinas Komunikasi, Informatika dan Statistik Provinsi Bengkulu of Communication, Information and Statistics. This application has features that are capable of managing and storing data starting from the Surat Perintah Perjalanan Dinas (SPPD), Surat Perintah Tugas (SPT) or Surat Perintah (SP), kwitansi, rincian biaya perjalanan dinas, nota dinas, bukti perjalanan dinas and approval carried out by superiors. The design and construction of this application is made with Waterfall software development methods, Unified Model Language (UML) to model the system, and use the PHP programming language with the CodeIgniter Framework and MySQL databases and other software